Servicios ambientales de los sistemas agroforestales - Beer, John; Harvey, Celia A.; Ibrahim, Muhammad Akbar; Harmand, Jean Michel; Somarriba, Eduardo; Jiménez Otárola, Francisco (CATIE, Turrialba (Costa Rica), 2015)
2 tablas, 65 ref.